PENYELESAIAN WANPRESTASI DALAM PELAKSANAAN PERJANJIAN ANTARA PT.PLN (Persero) DENGAN PELANGGAN DALAM PENGGUNAAN TENAGA LISTRIK DI KABUPATEN MAROS - , MONALISA; , Dr. Ari Hernawan, S.H, M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine how the settlement adopted by PLN in terms of customers in default. And efforts made by customers who are disadvantaged due to PLN service Maros Branch. The study was conducted at the location of PLN (Limited) Branch Maros Maros regency. This study relies on empirical juridical primary data as the primary data source. The research literature is also made to support the field data. Data was collected through direct interviews with respondents and informants. The analysis was done qualitatively the results are presented descriptively. The results showed that in the event of default undergo a form of late payments made by customers PLN (Ltd) will not immediately cut off the electricity customers. PLN is still giving time to its customers to excel. Termination directly carried out by PLN (Ltd) in terms of subscribers to electricity theft. The efforts made by the customer in terms of losses caused by the PLN service is to report directly to the PLN, but always get a poor response. Subscribers then complained the matter to the YLKI, where YLKI a consumer protection agency that has a big share in the fight for the protection of the rights of customers. Electricity customers are accompanied by YLKI expected to defend and fight for the rights of customers who neglected to make a lawsuit against PLN either through Consumer Dispute Settlement Body (BPSK) and in the courts through a class action.